Luminescent probe synthesis for oxygen visualization technique: Application to the effect of surfactant structure on oxygen mass transfer. (12th October 2022) - Lebrun, Gaëlle; El Mokdad, Bilal; Le Men, Claude; Pimienta, Véronique; Coudret, Christophe; Roux, Clément; Hébrard, Gilles; Dietrich, Nicolas
Highlights: Synthesis of a luminescent probe for oxygen tracking in aqueous solutions. New dye for Planar Laser Induced Fluorescence with Inhibition technique. Effect of the chain length of anionic surfactants on gas liquid oxygen transfer. Effect of surfactants adsorption on oxygen transfer. Predictive model for gas liquid oxygen transfer in the presence of surfactants. Abstract: Planar Laser Induced Fluorescence with Inhibition (PLIF-I) is a powerful technique for studying the local gas/liquid oxygen mass transfer from a single rising bubble. However, to track oxygen in the liquid phase, it is necessary to use an oxygen sensitive luminescent probe, which needs to be unreactive toward the liquid phase. This article presents the synthesis of a fluorophore, [Ru(dpp-diSO3 )3 ]Na4, to be used in liquid phases containing anionic molecules. To avoid electrostatic interactions, the fluorophore and the component present in the liquid phase need to have the same charge. Thanks to the use of this new luminescent probe in PLIF-I application, the influence of the chain length of anionic surfactants (dodecyl sulfate sodium salt and tetradecyl sulfate sodium salt) on oxygen mass transfer has been studied at different concentrations (1.3 × 10 -3 -2.5 × 10 -7 mol.L -1 ). Results show that, for a given bulk concentration, the longer the hydrophobic chain, the greater the decrease in velocity and mass transfer coefficient. These results are compared with those of a previous paper dealing with length of cationic and nonionic surfactants and a correlation is proposed, taking account of the intrinsic properties of surfactants and their concentration in the liquid phase.